Outcomes of laparoscopic bile duct exploration for choledocholithiasis with small common bile duct - Huang, Xiao-Xiao (World J Clin Cases, 2021)
BACKGROUND: Laparoscopic cholecystectomy (LC) combined with laparoscopic common bile duct (CBD) exploration (LCBDE) is one of the main treatments for choledocholithiasis with CBD diameter of larger than 10 mm. However, for patients with small CBD (CBD diameter ≤ 8 mm), endoscopic sphincterotomy remains the preferred treatment at present, but it also has some drawbacks associated with a series of complications, such as pancreatitis, hemorrhage, cholangitis, and duodenal perforation. To date, few studies have been reported that support the feasibility and safety of LCBDE for choledocholithiasis with small CBD. AIM: To investigate the feasibility and safety of LCBDE for choledocholithiasis with small CBD. METHODS: A total of 257 patients without acute cholangitis who underwent LC + LCBDE for cholecystolithiasis from January 2013 to December 2018 in one institution were reviewed. The clinical data were retrospectively collected and analyzed. According to whether the diameter of CBD was larger than 8 mm, 257 patients were divided into large CBD group (n = 146) and small CBD group (n = 111). Propensity score matching (1:1) was performed to adjust for clinical differences. The demographics, intraoperative data, short-term outcomes, and long-term follow-up outcomes for the patients were recorded and compared. RESULTS: In total, 257 patients who underwent successful LC + LCBDE were enrolled in the study, 146 had large CBD and 111 had small CBD. The median follow-up period was 39 (14-86) mo. For small CBD patients, the median CBD diameter was 0.6 cm (0.2-2.0 cm), the mean operating time was 107.2 ± 28.3 min, and the postoperative bile leak rate, rate of residual CBD stones (CBDS), CBDS recurrence rate, and CBD stenosis rate were 5.41% (6/111), 3.60% (4/111), 1.80% (2/111), and 0% (0/111), respectively; the mean postoperative hospital stay was 7.4 ± 3.6 d. For large CBD patients, the median common bile duct diameter was 1.0 cm (0.3-3.0 cm), the mean operating time was 115.7 ± 32.0 min, and the postoperative bile leak rate, rate of residual CBDS, CBDS recurrence rate, and CBD stenosis rate were 5.41% (9/146), 1.37% (2/146), 6.85% (10/146), and 0% (0/146), respectively; the mean postoperative hospital stay was 7.7 ± 2.7 d. After propensity score matching, 184 patients remained, and all preoperative covariates except diameter of CBD stones were balanced. Postoperative bile leak occurred in 11 patients overall (5.98%), and no difference was found between the small CBD group (4.35%, 4/92) and the large CBD group (7.61%, 7/92). The incidence of CBDS recurrence did not differ significantly between the small CBD group (2.17%, 2/92) and the large CBD group (6.52%, 6/92). CONCLUSION: LC + LCBDE is safe and feasible for choledocholithiasis patients with small CBD and did not increase the postoperative bile leak rate compared with chole-docholithiasis patients with large CBD.